Collecção de decretos e regulamentos publicados durante o governo da regencia do reino estabelecida na Ilha Terceira (Imprensa Nacional, 1834)
OCLC: 1021232315
Keywords: 12. Fragment; 18.Bookworm; 1828-1834; 2.Damage; 22.stamp; Condition: Poor; Droit Portugal; Hard Cover; History; Law; Law Portugal; Politics and government; Portugal; Portugal Histoire 1828-1834 (Michel Ier) Sources; Portugal History Miguel I; 1828-1834 Sources; Portugal Politics and government 1828-1834; Portugal Politique et gouvernement 1828-1834; Sources

Flore Française destinée aux Herborisations ou description des plantes croissant naturellement en France, ou cultivées pour l'usage de l'homme et des animaux : avec l'analyse des Genres et leur tableau d'après le systeme de Linné / 2. - Auguste Mutel (Levrault, 1834)
Condition: Binding: Stamps: Sinageture:
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; 8.Tear; Condition: Poor; Paperback; natural sciences

Institutiones Theologicae ad Usum Seminariorum - Bouvier, J. B (Apud Mequignon Juniorem, 1834)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Institutiones Theologicae ad Usum Seminariorum - Bouvier, J. B (Apud Mequignon Juniorem, 1834)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Institutiones Theologicae ad Usum Seminariorum - Bouvier, J. B (Apud Mequignon Juniorem, 1834)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

La Sainte Bible - Genoude, M. de (Pourrat Freres, 1834)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage